Transient ischemic attack characterized by external strabismus of the left eye: A case report. Issue 24 (June 2018) - Wang, Xue; Yu, Yang; Zhang, Wenxia; Meng, Hongmei
Abstract: Rationale: Patients rarely display eye movement dysfunctions as the primary symptom in transient ischemic attack. Patient concerns: A 58-year-old patient with a history of hypertension and smoking presented with a 1-month history of paroxysmal exotropia of the left eye and double vision. No obvious abnormality was found in imaging examination and the patient ignored his symptoms. Eleven days later, the symptoms worsened and brain imaging provided an abnormal signal involving the left cerebellar hemisphere and the bilateral occipital lobe. Diagnoses: Based on the clinical manifestation and imaging findings, an acute cerebral infarction was diagnosed. Interventions: The patient was subjected to antiaggregation therapy. Outcomes: One week later, the symptom of paroxysmal exotropia of the left eye was no longer present. Lessons: Atypical symptoms of transient ischemic attack are easy to be overlooked. Early diagnosis and timely treatments are keys to reverse the neurological symptoms and can be highly beneficial for patients with this condition.